EndoG links Bnip3-induced mitochondrial damage and caspase-independent DNA fragmentation in ischemic cardiomyocytes. - Jisheng Zhang; Junmei Ye; Albert Altafaj; Maria Cardona; Núria Bahi; Marta Llovera; Xavier Cañas; Stuart A Cook; Joan X Comella; Daniel Sanchis (PLoS ONE)
Mitochondrial dysfunction, caspase activation and caspase-dependent DNA fragmentation are involved in cell damage in many tissues. However, differentiated cardiomyocytes repress the expression of the canonical apoptotic pathway and their death during ischemia is caspase-independent. The atypical BH3-only protein Bnip3 is involved in the process leading to caspase-independent DNA fragmentation in cardiomyocytes. However, the pathway by which DNA degradation ensues following Bnip3 activation is not resolved. To identify the mechanism involved, we analyzed the interdependence of Bnip3, Nix and EndoG in mitochondrial damage and DNA fragmentation during experimental ischemia in neonatal rat ventricular cardiomyocytes. Our results show that the expression of EndoG and Bnip3 increases in the heart throughout development, while the caspase-dependent machinery is silenced. TUNEL-positive DNA damage, which depends on caspase activity in other cells, is caspase-independent in ischemic cardiomyocytes and ischemia-induced DNA high and low molecular weight fragmentation is blocked by repressing EndoG expression. Ischemia-induced EndoG translocation and DNA degradation are prevented by silencing the expression of Bnip3, but not Nix, or by overexpressing Bcl-x(L). These data establish a link between Bnip3 and EndoG-dependent, TUNEL-positive, DNA fragmentation in ischemic cardiomyocytes in the absence of caspases, defining an alternative cell death pathway in postmitotic cells.